Discharge characteristics of pre‐polarized doped lead zirconate titanate under impact at room and high temperature. Issue 3 (28th November 2021) - Wang, Ruizhi; Tang, Enling; Yang, Guolai; Han, Yafei; Chen, Chuang; Chang, Mengzhou; Guo, Kai; He, Liping
Abstract: Piezoelectric materials have more and more applications in modern smart fuzes due to their multiple uses such as energy storage and sensing. The electrical output characteristics of piezoelectric ceramics under high temperature and high overload environments are critical to the reliability of the device. In this paper, the mechanical and electrical response of pre‐polarized doped lead zirconate titanate (PZT‐5H) under impact at room temperature to 250°C, that is, above the Curie temperature, was investigated through a split‐Hopkinson pressure bar experiment with an additional electrical output measurement system. The depolarization effect caused by temperature and the mechanical load was analyzed. A thermoviscoelastic constitutive model considering temperature and the strain rate was built based on the experimental data. The model can successfully predict the mechanical and electrical response of PZT‐5H under impact at different temperatures. The discharge characteristics of PZT‐5H under impact in the cooling stage after high‐temperature depolarization were also investigated, and the apparent flexoelectric coefficient of the PZT after complete depolarization was calculated. The research results show that the dynamic piezoelectric coefficient of PZT‐5H has a nonlinear relationship with temperature. During the high‐temperature cooling process, PZT has a shock‐induced polarization under the impact, and the output voltage is less than the polarized piezoelectric ceramic but higher than the flexural polarization at the same temperature. After complete depolarization, the apparent flexoelectric coefficient of PZT‐5H is 127 μC/m.